Streptococcus sanguinis as an opportunistic bacteria in human oral cavity: Adherence, colonization, and invasion - Pramesti, Hening Tjaturina (Padjadjaran Journal of Dentistry, 2016)
Streptococcus sanguinis (formerly S. sanguis) is a Gram-positive, facultative anaerobe,Â  nonmotile , normalÂ  inhabitant of the human oral cavity, andÂ  a member ofÂ  the viridans group of streptococci. Among the streptococcus, S. sanguinis is aÂ  primary colonizer in the human tooth surface or it is recognize as a âpioneerâ by forming dental plaque. The aim of this paper is to review the role of Streptococcus sanguinisÂ  in the adherence to andÂ  invasion ofÂ  human tissues.Â  S. sanguinisÂ  has been reportedÂ  that it is associatedÂ  with healthyÂ  toothÂ  surfacesÂ  but not with caries. S. sanguinisÂ  tend to involved in an interspecies interactions with Streptococcus mutans, which is known asÂ  competition/coexistence within dental biofilm.Â  In their colonization, this bacteria used enzyme sortase A (SrtA) to cleaveÂ  LPXTG-containing proteins sequence andÂ  anchoredÂ  theÂ  cell wall, while virulence factorsÂ  in infective endocarditisÂ  involved housekeeping functions such as cell wall synthesis, amino acid and nucleic acid synthesis, and the ability to survive under anaerobic conditions.